Upaya Peningkatan Komunikasi Interprofesional Melalui Interprofessional Collaborative Practice (ICP) (Systematic Review) - Raihany Sholihatul Mukaromah; Luky Dwiantoro; Agus Santoso (Persatuan Perawat Nasional Indonesia Jawa Tengah, 2018)
The role and function of interdisciplinary care providers in health services is still fragmented so that interdisciplinary health services provided to patients become overlapping. Interdisciplinary fragmentation can be overcomed through Interprofessional Collaborative Practice (ICP). Good collaboration between the team of health professionals is needed, in order to exchange information clearly and comprehensively. The core competency in Interprofessional Collaborative Practice (ICP) is effective interprofessional communication. The purpose of this systematic review is to find out whether ICP can improve the ability of health workers to carry out interprofessional communication. The method used by Systematic review was by searching literature databases from Ebscho, Sciendirect, PubMed and Google scholar by using advanced search keywords. The keywords chosen were Interprofessional Collaborative Practice (ICP), Interprofessional Communication, health workers. The searching was limited in 2006 - 2016, full text pdf and English. The inclusion criteria from the article was the health workers as the respondents, intervention with Interprofessional Collaborative Practice (ICP), the outcome measured was interprofessional communication skills of health workers. There were 6 articles that correspond to the inclusion criteria. Those 6 articles were reviewed. Results: each article gives an outcome to the improvement of interprofessional communication and 2 articles produce 3 themes. ICP can effectively improve the ability of health workers to carry out interprofessional communication. It is expected that the head of the hospital can make a special policy related to the implementation of ICP and design a model for ICP involving all health professions so that it can be applied in health services as an effort to develop effective interprofessional communication and improve the quality of health services so that the professional role of each discipline runs well.